O microssistema de precedentes no Direito Processual Tributário - Cunha, Daniele Lambert da (2025)
This dissertation was carried out within the scope of the Graduate Program (Master's Degree) in Constitutional Law and Tax Procedure and uses the methodology of bibliographic review. The object of study is the impact of binding judicial decisions rendered by the STF in the judgments of extraordinary appeals with recognized general repercussion, and by the STJ in those of repetitive special appeals, in the tax sphere, for the promotion of legal certainty, the principle of isonomy, and for the resolution of conflicts. The justification for the choice of the theme stems from the importance of formalizing and observing these precedents, of national scope, in the understanding of the current law. To this end, it was necessary to understand the nuances of the interpretation of precedents, their overcoming, and the modulation of the effects of decisions, to verify whether the microsystem of precedents, in addition to fulfilling the purposes contained in the CPC, generates a reduction in massive litigation and mitigates access to higher courts. Evidently, there is no room for deepening the modulation of effects in tax matters, but considering that the modulation of the effects of decisions is sometimes necessary, the aspect has been mentioned in some emblematic cases. Thus, some themes were selected that are generally relevant to the understanding of the present work